Struktura arki Noego (Rdz 6,14-16) w pismach św. Augustyna - Kochanek, Piotr (Vox Patrum, 2025)
Augustine reconstructed the structure of Noah's ark on the basis of Gen 6:14-16 and the writings of several of his predecessors. This reconstruction had a great influence on subsequent generations of Latin ecclesiastical writers. On the one hand, the Bishop of Hippo gathered the achievements of his predecessors in this matter, and on the other hand, he added many important new elements. In this way, he created his own image of the structure of Noah’s Ark. However, this image is scattered throughout many of his writings. It could be said that Augustine returned to the issue of the structure of Noah’s Ark several times. The most important descriptions of this structure are presented in four of his works. In chronological order, they are: „Contra Faustum”, „De baptismo”, „De civitate Dei” and „Quaestiones in Heptateuchum”. Noteworthy passages on the structure of the ark are also in (in alphabetical order): „Contra Secundinum”, „De doctrina christiana”, „Enarrationes in Psalmos”, „Epistula ad Catholicos de secta Donatistorum”, „In Ioannis Evangelium tractatus CXXIV” and in „Sermones”. In general, Augustine's image of the structure of the ark was intended not only to „satisfy” the connoisseurs of biblical theology of his time, but also to satisfy the curiosity of ordinary people, for whom Noah’s Ark could be treated as some kind of interesting, biblical technical detail.